Psychometric Properties of the Belief in Divine Retribution Scale: Turkish Version, Validity, and Reliability Study in Turkey - Alagöz, Ece (Journal of religion and health, 2026)
Belief systems significantly influence individuals’ cognitive and emotional processes. Among these, belief in divine retribution notably affects moral behavior and provides a framework for interpreting life's challenges. This study aimed to adapt the Belief in Divine Retribution Scale (BDRS) into Turkish and to examine its psychometric properties in a Turkish sample. Convergent validity was further evaluated by investigating the relationship between the BDRS and religious obsessions. This methodological study included 425 participants aged 18 years and older residing in Turkey. The adaptation process involved translation, back-translation, expert review, and pilot testing. The adaptation process followed established guidelines for cross-cultural validation of religious and spiritual measures. Data were collected using the Belief in Divine Retribution Scale, the Penn Inventory of Scrupulosity (PIOS), and a demographic questionnaire. Construct validity was assessed through exploratory and confirmatory factor analyses, and reliability was measured using Cronbach's alpha (α). Convergent validity was analyzed with Pearson’s correlation coefficients. The Turkish version maintained the original scale structure and identified a two-factor model: belief in divine reward (seven items) and belief in divine punishment (three items). The scale explained 64.9% of the total variance (KMO = 0.916; Bartlett's test, p < 0.001). Confirmatory factor analysis showed acceptable model fit (χ2/df = 2.370; CFI = 0.960; RMSEA = 0.078). The overall scale demonstrated high internal consistency (Cronbach's α = 0.911). The subscales' Cronbach's alpha coefficients were 0.889 for Reward Belief and 0.799 for Punishment Belief. A significant positive correlation was found between belief in divine retribution and religious obsessions (r = 0.426, p < 0.001). These results support the validity and reliability of the Turkish version of the Belief in Divine Retribution Scale. It can be used to assess individuals’ religious belief structures and their tendencies toward religious obsessions.